Biennale of Sydney 2006 - Abdullah, Sarena (2007)
THE 2006 BIENNALE OF SYDNEY (BoS) featured about 85 artists from 44 countries of diverse cultures: Bosnia, Malaysia, Palestine, japan, India, Canada, Lebanon, Singapore, Britain, Egypt, Latvia, China, Serbia & Montenegro, Bahrain, Russia, The Netherlands, Brazil, the United States, Xew Zealand and Kazakhstan. Held from 8 june until 27 August 2006, it took place at 16 venues spanning from Circular Quay to Marrickville, Blacktown and Campbelltown. Inspired by the Venice Bicnnalc and established in 1973, the BoS celebrated its 15th anniversary this year. Besides paintings, installa tions, performances, video and photographic works, the BoS also organized events such as artist talks, symposia and various public programs.